Inactivation and Recovery of High Quality RNA From Positive SARS-CoV-2 Rapid Antigen Tests Suitable for Whole Virus Genome Sequencing - Macori, Guerrino; Russell, Tristan; Barry, Gerald; McCarthy, Siobhán C.; Koolman, Leonard; Wall, Patrick; Sammin, Donal; Mulcahy, Grace; Fanning, Séamus (Frontiers in Public Health, 2022)
The diagnostic protocol currently used globally to identify Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection is RT-qPCR. The spread of these infections and the epidemiological imperative to describe variation across the virus genome have highlighted the importance of sequencing. SARS-CoV-2 rapid antigen diagnostic tests (RADTs) are designed to detect viral nucleocapsid protein with positive results suggestive of the presence of replicating virus and potential infectivity. In this study, we developed a protocol for recovering SARS-CoV-2 RNA from “spent” RADT devices of sufficient quality that can be used directly for whole virus genome sequencing. The experimental protocol included the spiking of RADTs at different concentrations with viable SARS-CoV-2 variant Alpha (lineage B.1.1.7), lysis for direct use or storage. The lysed suspensions were used for RNA extraction and RT-qPCR. In parallel, we also tested the stability of the viral RNA in the RADTs and the RNA extracted from the RADTs was used as a template for tiling-PCR and whole virus genome sequencing. RNA recovered from RADTs spiked with SARS-CoV-2 was detected through RT-qPCR with Ct values suitable for sequencing and the recovery from RADTs was confirmed after 7 days of storage at both 4 and 20°C. The genomic sequences obtained at each time-point aligned to the strain used for the spiking, demonstrating that sufficient SARS-CoV-2 viral genome can be readily recovered from positive-RADT devices in which the virus has been safely inactivated and genomically conserved. This protocol was applied to obtain whole virus genome sequence from RADTs ran in the field where the omicron variant was detected. The study demonstrated that viral particles of SARS-CoV-2 suitable for whole virus genome sequencing can be recovered from positive spent RADTs, extending their diagnostic utility, as a risk management tool and for epidemiology studies. In large deployment of the RADTs, positive devices could be safely stored and used as a template for sequencing allowing the rapid identification of circulating variants and to trace the source and spread of outbreaks within communities and guaranteeing public health.